Fast and Accurate 3D Scanning Using Coded Phase Shifting and High Speed Pattern Projection - Wissmann, P.; Schmitt, R.; Forster, F. (2011 International Conference on 3D Imaging, Modeling, Processing, Visualization and Transmission, 2011)
We describe a structured light phase measuring triangulation technique extending the conventional four-step phase shift sequence with embedded information suited to assist the phase unwrapping process. Using the embedded information, we perform automatic phase unwrapping in the presence of discontinuous or isolated surfaces without extending the length of the phase shift sequence or requiring stereo cameras. We demonstrate the application of the proposed method using a novel structured light projector capable of extraordinarily high projection frequencies and pattern resolution, as well as grayscale quantization. Using high speed cameras, we demonstrate 3D measurements at 20ms total acquisition time for both mono- and stereoscopic camera configurations.